Associations between dysbiosis-inducing drugs, overall survival and tumor response in patients treated with immune checkpoint inhibitors. (March 2021) - Gaucher, Louis; Adda, Leslie; Séjourné, Alice; Joachim, Camille; Guillaume, Chaby; Poulet, Claire; Liabeuf, Sophie; Gras-Champel, Valérie; Masmoudi, Kamel; Houessinon, Aline; Bennis, Youssef; Batteux, Benjamin
Background: There are conflicting data on the effects of dysbiosis-inducing drugs, and especially antibiotics (ATBs), on clinical outcomes in patients treated with immune checkpoint inhibitors (ICIs). There is a particular lack of data for patients with melanoma. Methods: We performed a single-center retrospective study of the associations between ATBs and other drugs known to modify the gut microbiota (proton pump inhibitors, nonsteroidal anti-inflammatory drugs, statins, opioids, anti-vitamin K, levothyroxine, vitamin D3, antiarrhythmics, metformin and phloroglucinol), overall survival (OS) and tumor response in consecutive cancer patients (particularly those with melanoma) treated with an ICI (ipilimumab, nivolumab or pembrolizumab) over a 9-year period. Results: A total of 372 patients were included. The mean ± standard deviation age was 64.0 ± 12.1 years. The most frequently prescribed ICI was nivolumab (in 58.3% of patients) and the most frequent indications were lung cancer (44.6%) and melanoma (29.6%). Overall, 112 patients (30.1%) had received ATBs. ATB use was associated with (1) shorter OS in the study population as a whole [adjusted hazard ratio [95% confidence interval (CI)]: 1.38 (1.00–1.90), p  = 0.048] and in patients with melanoma [adjusted hazard ratio (95% CI): 2.60 (1.06–6.39), p  = 0.037], and (2) a lower response rate in the study population as a whole [8.1%, versus 31.1% in patients not treated with ATBs; adjusted odds ratio (95% CI): 6.06 (2.80–14.53), p  < 0.001] and in patients with melanoma [adjusted odds ratio (95% CI): 4.41 (1.04–22.80), p  = 0.045]. Sensitivity analyses that minimized the indication bias did not reveal an association between OS and the presence of an infection requiring ATBs (quantified as the severity of infection, hospitalization for an infection, or ICI discontinuation). Other dysbiosis-inducing drugs were not associated with a difference in OS. Conclusion: Unlike other dysbiosis-inducing drugs, ATBs were associated with poorer clinical outcomes in ICI-treated patients overall and in the subset of patients with melanoma.